2008
DOI: 10.1016/j.febslet.2008.05.002
|View full text |Cite
|
Sign up to set email alerts
|

p3 peptide, a truncated form of Aβ devoid of synaptotoxic effect, does not assemble into soluble oligomers

Abstract: In previously proposed models of A beta soluble oligomers, the N-terminal domain A beta(1-16), which is missing in p3 peptides, protects the hydrophobic core of the oligomers from the solvent. Without this N-terminal part, oligomers of p3 peptides would likely expose hydrophobic residues to water and would consequently be less stable. We thus suggest, based on theoretical and experimental results, that p3 peptides would have a low propensity to assemble into stable oligomers, evolving then directly to fibrilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 40 publications
2
28
1
Order By: Relevance
“…Our findings of neurotoxicity, channel formation, and increased neuronal calcium uptake by p3 and N9 are consistent with the work of Pike et al (24), who showed that these N-terminally truncated peptides demonstrated enhanced aggregation, neurotoxicity, and fibrilformation. p3 has been reported not to form "soluble oligomers" (36) and our present results support the notion that p3 oligomerizes directly in the membrane to cause toxicity. However, in a double transgenic mouse study with overexpressed ADAM10 and human APP that increased α-secretase activity, AD initiation and progression were limited (37).…”
Section: Discussionsupporting
confidence: 81%
“…Our findings of neurotoxicity, channel formation, and increased neuronal calcium uptake by p3 and N9 are consistent with the work of Pike et al (24), who showed that these N-terminally truncated peptides demonstrated enhanced aggregation, neurotoxicity, and fibrilformation. p3 has been reported not to form "soluble oligomers" (36) and our present results support the notion that p3 oligomerizes directly in the membrane to cause toxicity. However, in a double transgenic mouse study with overexpressed ADAM10 and human APP that increased α-secretase activity, AD initiation and progression were limited (37).…”
Section: Discussionsupporting
confidence: 81%
“…Because it uses an antibody directed to A␤'s N-terminal amino acid residues, it cannot discriminate between A␤1-40, A␤1-42, other A␤ degradation products, and p3 peptide, which is derived from the non-amyloidogenic pathway of APP processing (Dulin et al, 2008). Further, it cannot distinguish large numbers of small oligomers from smaller numbers of large oligomers.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies indicate that Ab17-42 exhibits enhanced aggregation relative to full-length Ab42 26 and that p3 peptides are prevalent in diffuse deposits and in a subset of dystrophic neurites in AD patients. 27 However, other studies suggest that p3 peptides might be a benign form of amyloid because they lack domains associated with microglial activation, 28 do not form oligomers, the most toxic species of Ab, 18 and do not have negative effects on neuronal synaptic function. 29 Our present study demonstrates that p3 peptides compete with Ab42 for binding to fibrinogen, suggesting that they may attenuate AD pathology.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory efficacy of Ab17-42 was confirmed via pulldown assay, where pulldown of fragment D by biotinylated Ab42 was dose-dependently decreased in the presence of nonbiotinylated Ab17-42 ( Figure 2B). Our AlphaLISA and pulldown results indicate that Ab17-40 and Ab17-42, naturally occurring Ab fragments known as p3 peptides, 18 inhibit the Ab42-fibrinongen interaction, suggesting that these peptides may play a physiological role in modulating Ab42-mediated effects on fibrin clots.…”
Section: Identification Of the Fibrinogen-binding Region Within Ab42mentioning
confidence: 99%